(untitled) (Grande Medical Journal, 2021)
Introduction: A good predicting scoring system for intracerebral hemorrhage (ICH) has been a concern for decades, as this will help in guiding the treatment and prognostication. The most widely accepted one is the Hemphill ICH score, but this conventional scoring system requires complex memorization and calculation making it difficult to apply in clinical practice. Hence, there is a need for a simpler and more accurate scoring system for ICH for prognosis that can be readily determined. This study was undertaken to compare simple scoring systems, such as WFNS, GVS and ICH scores, in predicting in-hospital mortality and outcomes at discharge and at three months in patients with spontaneous ICH. This study was carried out in the Department of Neurosurgery and Department of Neurology, Tribhuvan University Teaching Hospital, Kathmandu, Nepal. Materials and Methods: Patients with primary spontaneous ICH aged ≥ 16 years admitted in the Department of Neurosurgery and Neurology participated in the study. The ICH, WFNS and GVS scores were measured at the earliest possible time during admission by a single observer. Modified Rankin scale (mRS) was measured at discharge and at three-months follow up. Mortality was used as the primary outcome measure. Results: A total of 130 patients were included in the study. The mean age of the study population was 60.7 ± 16 years. There was an increase in mortality rate among ICH cases with higher scores of ICH, WFNS and GVS. The area under ROC curve for ICH, WFNS and GVS scores for prediction of mortality was 0.895 (95 % CI; 0.838 - 0.952; p < 0.001), 0.876 (95 % CI; 0.813 - 0.938; p < 0.001) and 0.887 (95 % CI; 0.823 - 0.950; p < 0.001), respectively, suggesting a good discrimination ability of all these three scores in predicting death. All three scores showed good discrimination ability of good outcomes but only fair prediction of bad outcome. Conclusions: Both GVS and WFNS scores are simple, easy to use and comparable to ICH score for the prediction of mortality and good outcome in patients with spontaneous ICH. All three scores are inferior for the prediction of bad outcome. ICH score is marginally better than other two scores in all outcome subgroups but was not statistically significant. In all three outcomes, ICH score was marginally better but comparable with the other two scores.